Análisis de zonas susceptibles ante la amenaza de inundaciones, empleando SIG en el recinto Charquiyacu, cantón Caluma, período noviembre 2022-febrero 2023 - Puentestar Quishpi, Henry Rodrigo (2023)
The present investigation had as objective to analyze the susceptible areas before the threat of floods, using Geographic Information Systems in the recinto Charquiyacu, cantón Caluma, due to the fact that floods become the most frequent problem in the town due to its irregular topography and oscillating weather. In addition, the threat of floods that is latent in the territory brings significant losses and fear to the population, specifically in the winter season. The methodology proposed by the National Secretary "SNGR, 2017" was used, in order to determine areas prone to flooding, which considers natural and anthropic factors, through the use of ArcGis 10.8 Software and Shapes of each of the factors of susceptibility. Based on the flood susceptibility map of the recinto Charquiyacu, the results indicate that the threat of flooding in the recinto Charquiyacu is at a very high and high vulnerability level; Consequently, the correlation indicates that: the buildings in the study area present a very high level of vulnerability, equal to 88.8%; the essential buildings: the health center, the church and the bridge have a very high vulnerability level, equivalent to 75%, the Dr. Alfredo Noboa Montenegro Educational Unit has a high vulnerability level, equivalent to 25% and The road system presents a level of vulnerability, very high, equivalent to 82.33%. Finally the strategies for reducing areas prone to flooding are: dredging the Rio Charquiyacu, reinforcing retaining walls, building gabion walls, land use planning, training, and the preparation of hazard maps. Keywords: Threat, susceptibility, anthropic factors, natural factors, floods, preparation